STUDENT ENGAGEMENT IN ONLINE LEARNING IN INFERENTIAL STATISTICS COURSES - Winda Hurotul ‘Aini (Nusantara Hasana Journal, 2025)
This study explores the dynamics of student engagement in online learning environments for inferential statistics courses. With the shift to digital platforms, maintaining active participation and sustained interest in mathematically intensive subjects has emerged as a critical challenge. The research employs a mixed-method approach, combining quantitative surveys and qualitative interviews, to analyze cognitive, emotional, and behavioral engagement among students. Key factors such as instructional design, technological tools, and peer interaction are evaluated to understand their impact on learning outcomes. Findings indicate that interactive content, regular feedback, and collaborative activities significantly enhance engagement, while technological challenges and lack of motivation serve as primary barriers. The study offers practical recommendations for educators, focusing on adaptive learning strategies, gamification, and personalized support to foster deeper engagement. These insights contribute to improving online pedagogy in inferential statistics, ensuring that students remain motivated and achieve academic success in virtual settings.